How stakeholders affect the pursuit of the Environmental, Social, and Governance. Evidence from innovative small and medium enterprises. (30th July 2021) - Esposito De Falco, Salvatore; Scandurra, Giuseppe; Thomas, Antonio
Abstract: ESG has become particularly relevant and widespread among a growing number of firms. This dynamic is the consequence of different solicitations to which companies are subject, mainly by stakeholders. To pursue ESG usually requires the implementation of eco‐innovations (EI). Until now, literature about the effects of EI on ESG has been predominantly focused on large corporations, while little attention has been paid to SME, particularly to innovative SMEs. Within the ESG framework, this paper investigates how stakeholders influence innovative SME decisions to adopt EIs. To reach this aim, we investigate a probabilistic sample of 222 SMEs using the Partial Least Squares method. Results highlight that contractual stakeholders exert a higher influence than community stakeholders on EI. Among the single stakeholders belonging to the mentioned categories, only investors/lenders do not exert influence.